UNDERSTANDING THE IMPACT OF RECOGNITION AND RECALL ACTIONS ON ARCHITECTURAL DESIGN PROCESS - Noor Saeed; Can Uzun (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi)
Every architect has a personal archive of pictures and details that they use to help them develop their architectural design that, for the most part, embodies their vocabulary within their memory from earlier experiences. The retrieval mechanism for these experiences is vital in the design process. This study examines the relationship between retrieval and design action, particularly through the specified codes: recall, recognize, guess, propose, analyze, and evaluate to understand the underlying design strategies based on these retrieval actions. This study applies the investigate-and-redesign method to reveal the retrieval and design action patterns and conducts protocol analysis through the think-aloud procedure. We use a two-stage quasi-experiment method for “investigate and redesign” parts. In the investigate part, subjects study the twenty given building facade images, and in the redesign part, subjects are asked to design a new facade, and they are allowed to apply free recall from the studied examples. Results show that designers are shifting or modifying their strategies on retrieval and design actions to minimize the error rates in design and accomplish the task in a given time. Design actions are more focus-demanding than retrieval actions. Retrieval actions appear with free associations, and focus shifts occur frequently in retrieval actions. All the codes of retrieval action and proposed code of design action are associated. Overall, this study reveals the nature of the occurrence pattern between retrieval and design actions by providing different design strategies for different retrieval actions.